Neuromedin U alters bioenergetics and expands the cancer stem cell phenotype in HER2‐positive breast cancer. Issue 12 (26th April 2017) - Martinez, Vanesa G.; Crown, John; Porter, Richard K.; O'Driscoll, Lorraine
Abstract : Neuromedin U (NmU) is a neuropeptide belonging to the neuromedin family. Recently, we reported a significant association between NmU and breast cancer, particularly correlating with increased aggressiveness, resistance to HER2‐targeted therapies and overall significantly poorer outcome for patients, although the mechanism through which it exerts this effect remained unexplained. Investigating this, here we found that ectopic over‐expression of NmU in HER2‐positive breast cancer cells induced aberrant metabolism, with increased glycolysis, likely due to enhanced pyruvate dehydrogenase kinase activity. Similar results were observed in HER2‐targeted drug‐resistant cell variants, which we had previously shown to display increased levels of NmU. Overexpression of NmU also resulted in upregulation of epithelial‐mesenchymal transition markers and increased IL‐6 secretion which, together with aberrant metabolism, have all been associated with the cancer stem cell (CSC) phenotype. Flow cytometry experiments confirmed that NmU‐overexpressing and HER2‐targeted drug‐resistant cells showed an increased proportion of cells with CSC phenotype (CD44 + /CD24 – ). Taken together, our results report a new mechanism of action for NmU in HER2‐overexpressing breast cancer that enhances resistance to HER2‐targeted drugs through conferring CSC characteristics and expansion of the CSC phenotype. Abstract : What's new? Cancer cells exhibit various metabolic adaptations, which contribute to tumor aggressiveness and drug resistance and are a prerequisite for stemness. The link between metabolic abnormalities and stemness in cancer cells, however, is not fully understood. Here, increased stemness in HER2‐positive breast cancer cells was associated with overexpression of neuromedin (NmU), a neuropeptide with functions in energy homeostasis. Ectopic and induced NmU overexpression resulted in increases in the proportion of cells with cancer stem cell (CSC) phenotypes and in key markers associated with CSC phenotype. The findings suggest that NmU could be a valuable therapeutic target in HER2‐positive breast cancer.